Exploring my role modelling as a teacher educator: A self-study - Hiralaal, A. (South African Journal of Higher Education, 2018)
My self-study involved an exploration of my role modelling as a teacher educator of accounting pedagogy. I became aware that there seemed to be a living contradiction in my practice. I suspected my educational values were not being adequately played out in my teaching when students told me they teach as I teach them. Therefore, the purpose in undertaking this research was to align my teaching with my educational values in order to improve my practice by developing as a more productive role model. To improve my practice, I adopted a social constructivist student-centred approach in my teaching and enacted purposeful pedagogies. I used a self-study methodological approach to generate data. Working with students, colleagues and critical friends and the educative conversations I had, I constructed my living educational theory which reflected the human reality of my work because it was grounded in my embodied values